3D Design of chemistry subject at UTeM : Atom cubic - Mohd Hatta, Nuraziera; Bakar, Norasiken (2011)
This research highlights the development of 3D approach in learning for chemistry subject. Chemistry is one of the compulsory subjects for all undergraduate students in science fields. There are a number of methods to deliver chemistry lessons especially in classes of basic molecular formation theories. Throughout the years, various teaching methods have been adopted to assist students to better understand in learning chemistry subject. Current knowledge delivery in education is dynamically changing to more flexible and reliable. This research attempt to alternatively present new ways of learning chemistry subject by using 3D approach to encounter the problems found from the survey and interview done.